MARKETING EFFECTIVENESS IN NIGERIAN CONSTRUCTION: STRATEGIES AND INSIGHTS - Adebayo , Oluwaseun Adediran; Okafor, Chinedu Emmanuel (International Journal of Allied Research in Marketing and Management (IJARMM), 2024)
Marketing is a global practice essential for the survival and growth of companies, emphasizing the need to align products and services with customer demands (Waugh, 2004; Arslan et al., 2009). Effective marketing is particularly crucial in competitive environments, where it significantly impacts overall business success (Polat and Donmez, 2010). However, the construction industry has historically undervalued marketing as a management function. Many constructions professionals regard marketing as non-essential, leading to its minimal integration into organizational structures and slow adoption where it is included (Winter and Preece, 2000; Bennett, 2005; Jaafar et al., 2008; Arslan et al., 2009). This paper explores the significance of marketing in the construction sector, examining how effective marketing strategies can enhance business performance and competitive edge. The study underscores the need for greater emphasis on marketing within construction firms to drive growth and adapt to evolving market demands